2010
DOI: 10.4314/ajtcam.v6i4.57220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hypoglycemic activity of the polysaccharides extracted from <i>Lycium barbarum</i>

Abstract: A study was undertaken to evaluate the hypoglycemic activity of polysaccharide extracted from Lycium barbarum (LBP). The various parameters studied included body weight (bw), fasting blood glucose levels (FBG), total cholesterol (TC) and triglyceride (TG) in diabetic and normal mice. LBP treatment (20, 40 mg/ kg body weight) for 28 days resulted in a significant decrease in the concentration of FBG, TC and TG in diabetes mellitus mice. Furthermore, LBP significantly increased body weight. The data demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 7 publications
1
25
0
2
Order By: Relevance
“…Pretreatment with L-arginine partially restored acetylcholine-induced relaxation in hypertensive rats, but no effect in LBP-treated rats. LBP treatment resulted in a significant decrease in the concentration of fasting blood glucose levels, total cholesterol and triglyceride in diabetes mellitus mice (Jing, Cui, Feng, & Xiao, 2009).…”
Section: Cardiovascular Benefitsmentioning
confidence: 90%
See 1 more Smart Citation
“…Pretreatment with L-arginine partially restored acetylcholine-induced relaxation in hypertensive rats, but no effect in LBP-treated rats. LBP treatment resulted in a significant decrease in the concentration of fasting blood glucose levels, total cholesterol and triglyceride in diabetes mellitus mice (Jing, Cui, Feng, & Xiao, 2009).…”
Section: Cardiovascular Benefitsmentioning
confidence: 90%
“…The decreased activation of extracellular signal-regulated kinases 1 and 2 in mesangial cells, through the involvement of protein kinase C, may explain the protective mechanism in kidneys of diabetic rats treated with LBP (Zhao, Li, Li, & Zhang, 2009). LBP treatment also resulted in a significant decrease in the concentration of fasting blood glucose levels, total cholesterol and triglyceride in diabetes mellitus mice (Jing et al, 2009).…”
Section: Animal Experimentsmentioning
confidence: 93%
“…Another positive finding regarding the use of Goji berry was found by Jing et al (2009). According to the authors, the use of LBP-4 in diabetic rats showed a decrease in total cholesterol and triglycerides levels.…”
Section: Discussionmentioning
confidence: 93%
“…84 Hyoscyamys albus: Calystegines (A 3 , A 5 , A 5 glycosides, B 1 , B 2 , B 4 , N 1 ) that was isolated from H. albus seeds are potent anti-diabetic agents with antihyperglycemic and hypolipidemic effects, and a protective function on pancreas in streptozotocin induced diabetes. 85 …”
Section: Solanaceaementioning
confidence: 99%